Study of expired Fuclo 500 drug as an environmentally sustainable corrosion inhibitor - Koffi, Aphouet Aurelie; Allou, N'guadi Blaise; Tigori, Mougo Andre; Soro, Teminfolo Yaya; Trokourey, Albert; Niamien, Paulin Marius (European Journal of Chemistry, 2023)
This work deals with aluminium corrosion inhibition by expired drugs containing flucloxacillin in 1 M hydrochloric acid medium, using the gravimetric method and density functional theory. Weight loss results showed that the inhibitory efficiency of this compound increases with concentration and decreases with increasing temperature. The study also indicates that this molecule is adsorbed according to the modified Langmuir model (Villamil model). Furthermore, the thermodynamic parameters of adsorption (∆Goads, ∆Hoads, ∆Soads) and activation (Ea*, ΔHa*, ΔSa*) show that the adsorption is mixed type (chemisorption and physisorption). In addition, density functional theory provides access to the quantum chemical parameters of the molecule such as the lowest vacant orbital energy (ELUMO), the highest occupied orbital energy (EHOMO), the absolute electronegativity (χ), the global hardness (η), the global softness (S), the fraction of transferred electrons (ΔN) as well as the electrophilicity index (ω) for finding correlation between the inhibitor structure and the experimental data.